Feasibility Study of Development Result of Interactive Flash Oriented Self-Regulated Learning Model Based Scientific - Erie Agusta (Jurnal Cakrawala Pendidikan, 2018)
This study investigated the feasibility of the scientific-based self-regulated learning model oriented interactive flash for the Biology subject from the perspective of experts. This study used descriptive qualitative method. Interviews with structured interview guidelines were used to collect the data in this study. Three groups of experts were employed in this study, i.e. materials, media, and language experts. The material experts examined the content of the interactive flash; the media experts examined the graphic and the clarity of the SLRBS models steps in the interactive flash; and the language experts examined the language aspects displayed in the interactive flash. Interactive analysis models were used in the data analysis. The analysis consisted of data collection, data reduction, data display, and conclusions. The findings showed that seven out of the 32 feasibility indicators needed revisions. The material aspects which needed revisions were the depth and coverage of the materials and the encouragement of curiosity and asking ability. The media aspects which needed revisions were image arrangement indicator and media . The language aspect which needed revisions was the sentence accuracy indicator since there were a few incorrectly written sentences in the flash presentation. It was concluded that the developed interactive flash media was categorized as feasible but still requires some revisions. Keywords: media, flash, Based Scientifi- Self-Regulated Learning STUDI KELAYAKAN HASIL PENGEMBANGAN FLASH INTERAKTIF BERORIENTASI MODEL SELF REGULATED LEARNING BERBASIS SAINTIFIK Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana kelayakan hasil pengembangan media flash interaktif Biologi berorientasi model self-regulated learning berbasis saintifik jika ditinjau dari sisi expert judgment. Penelitian ini menggunakan metode deskriptif kualitatif. Teknik pengumpulan data menggunakan wawancara. Intrumen penelitian menggunakan lembar wawancara terstruktur. Expert yang digunakan terdiri dari tiga kelompok, yakni expert materi, media, dan bahasa. Expert materi membahas aspek kelayakan isi flash, expert media membahas aspek kelayakan kegrafikan dan kejelasan langkah model SLRBS di dalam flash, dan expert bahasa membahas aspek kelayakan bahasa yang ditampilkan oleh media flash. Teknik analisis data menggunakan analysis interactive model yang terdiri dari data collection, data reduction, data display, dan conclusions. Hasil penelitian menggambarkan bahwa dari 32 indikator kelayakan hanya 7 indikator yang terindikasi revisi. Aspek materi yang diperbaiki adalah indikator kedalaman, keluasan materi, mendorong keingintahuan, dan mendorong kemampuan bertanya. Aspek media yang menjadi perbaikan adalah indikator penataan gambar, dan tingkat interaktif media dengan peserta didik. Aspek bahasa yang perlu direvisi adalah indikator ketepatan struktur kalimat karena ada beberapa kalimat yang salah tulis dalam penyajiannya. Simpulan penelitian ini adalah media flash yang dikembangkan terkatagori layak namun masih memerlukan revisi dibeberapa indikator.Kata kunci: media, flash, Self-Regulated Learning Berbasis Saintifik (SRLBS)